Naturalidade e vínculos teóricos para a massa do boson de Higgs - Alexandre Rodrigues Vieira (2012)
The Naturalness problem is a consequence of theories with scalar elds like the Standard Model. In these theories, the correction to the mass of the scalar is proportional to the energy scale squared and, consequently, this correction can be arbitrarily large in the ultraviolet limit. However, we argue this energy scale squared is related to an inadequate regularization scheme used to treat a quadratic divergent integral in that limit. In this work, we use Implicit Regularization to regularize one loop corrections to the Higgs propagator and the arbitrariness of divergent integrals in the ultraviolet limit to assure the absence of that energy scale squared by physical considerations. These physical considerations are chosen to be Naturalness and consistency of scale symmetry breaking. After we show there is no quadratic correction in the energy scale to the Higgs mass, we consider the corrections which do not violate the physical considerations to estimate the limit of validity of perturbation theory of the Standard Model and to nd bounds that restrict values to the Higgs mass in a diagram of Higgs mass versus energy scale.